Gravity Model–Based Export Potential : An Application to Turkey - Mulabdic, Alen; Yasar, Pinar (World Bank, Washington, DC, 2021)
This paper presents a framework to study countries’ export potentials. It uses a gravity model to develop measures of export and trade policy potentials at the aggregate, bilateral, and industry levels. The methodology is applied to the case of Turkey. The analysis finds that Turkey was moderately under-exporting over 2010-17. The United States, China, and Japan are important untapped destination markets, accounting for US$29 billion (16-17 percent of total exports) of missing exports. Industry-level results suggest that Turkey has high export potential in the electronics and chemical industries.